Role of Boarding School in Improving Arabic Language Skills - Ubadah Ubadah; Rizki Parahita Anandi (LISANIA: Journal of Arabic Education and Literature, 2022)
This research is focused on the role of boarding school to improve students' Arabic language skills at MAN 2 Palu. It is aimed at exploring the steps to improve their language skills and the methods and strategies used to improve Arabic language skills. The study uses field research with a qualitative descriptive design combined with observation data, interviews, and documentation. The results of the study indicate that the role of boarding schools is very big in improving the ability of students ability to speak Arabic with well-organized and steps such as tutoring activities in the afternoon and evening, habituation in Arabic, memorizing mufradât at dawn, giving sanctions in the form of memorizing vocabulary, and the existence of a language improvement team that works to monitor participants' discipline in using Arabic. The discussion method in learning Arabic, and the grammar and translation method  in the guidance of the kitab kuning study at night. While the strategy used is to provide a lot of linguistic exercises, such as Arabic speech and drama exercises in Arabic.